Digital Da'wah: Buya Yahya's Influence on YouTube, Facebook, and Instagram - Misbahuddin Z, Muhammad Fachri; Kahmad, Dadang; Wibawa, Darajat; Mukarom, Zaenal (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyze Buya Yahya's da'wah strategies through social media platforms YouTube, Facebook, and Instagram by focusing on the integration of communication patterns, audience interaction, and the overall effectiveness of da'wah in the digital age. The research employs a descriptive qualitative approach using content analysis and interview techniques. The findings reveal that Buya Yahya's da'wah across these three platforms adapts to the technical logic and user culture of each medium. YouTube is utilized for delivering in-depth and educational lectures, Facebook is optimized for interactive engagement and real-time responses to contemporary issues, while Instagram targets younger audiences with short, emotive, and visually driven messages. The discussion draws on the theoretical frameworks of Hypermediated Religion and Platformization of Religion, which emphasize that digital da'wah is not merely disseminated through various media, but also mediated and reshaped through user interactions and platform algorithms. The study concludes that Buya Yahya’s approach successfully integrates cross-platform da'wah strategies that are both participatory and adaptive to the needs of digital religious communities. This research offers both theoretical and practical contributions to the development of contemporary digital da'wah models that are not only communicative but also transformative in fostering contextual religious awareness.